Role of the beam profile and sample geometry in the bonded-disk method on the shrinkage kinetics of two dental resins. Issue 8 (August 2016) - Kostylev, I.; Winters, T.; Labrie, D.; Price, R.B.T.
Highlights: Real time imaging of the two dimensional (2D) axial shrinkage field in the bonded disk geometry is presented for two resin-based composites (RBCs). The time-dependent 2D axial shrinkage field depends strongly upon the light curing unit beam profile, sample geometry, and RBC visco-elastic properties. For a uniform beam profile and conventional sample geometry, the axial 2D shrinkage strain is uniform to within 4% over the central part of the sample. Abstract: Objective: To investigate the time evolution of the two dimensional axial shrinkage field for two dental resins in the bonded disk geometry and further test the bonded-disk method. Methods: An interferometric technique employing a camera was used to image the 2D axial shrinkage field when polymerizing dental resins in real time both during and after light exposure. Four different beam profiles from two light curing units and three sample geometries were utilized to investigate their roles on the 2D axial shrinkage field. Results: The 2D axial shrinkage field correlates qualitatively with the beam profile shortly after the start of light exposure but takes on distinct shapes caused by the rigidity of the coverslip, beam profile, and the resin viscoelasticity. Significance: Using the conventional bonded disk geometry and uniform beam profile from a light curing unit, the axial 2D shrinkage field was uniform to within 4% in the central part of bonded disk samples.